Panorama Poligami dan Resistensi Perempuan di Langsa Aceh - Muhammad Ansor (Ulumuna, 2012)
This article is an attempt to analyze the practice of polygamy and women’s resistance in Langsa. It will describe the stand point of the women involved in polygamy in their effort to renegotiate their understanding on the Islamic legal ruling on polygamy through their daily activities. By applying socio-anthropology approach, it found that there are two types of resistance: hidden and opened. Hidden resistance (hidden trancript) is revealed through various expressions, such as tarnishing the good name of the spouse or the second wife, pretending to be obedience while doing other wise, or confronting the spouse’s ruling on handling the household. Opened resistance (public transcript) is carried out in two ways, either by asking a divorce before the second marriage takes place, or after, when the second marriage is carried out without the consent of the first wife. Finally, this article argues that the resistance expression of the women involved in polygamy is in fact part of their resistance effort against the dominant interpretation of the legal ruling of polygamy in Islam.